2019
DOI: 10.1111/bph.14765
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap‐microparticle complexes trigger neutrophil recruitment via high‐mobility group protein 1 (HMGB1)‐toll‐like receptors(TLR2)/TLR4 signalling

Abstract: Background and Purpose Recent data suggest that neutrophil extracellular traps (NETs) form aggregates with microparticles (MPs) upon activation of neutrophils although the functional role of NET‐MP complexes remain elusive. The objective of this study was to examine the role of NET‐MP aggregates in leukocyte recruitment in vivo. Experimental Approach PMA stimulation of murine bone marrow neutrophils generated NET‐MP complexes and pretreatment with caspase and calpain inhibitors resulted in the formation of NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 67 publications
(93 reference statements)
0
29
0
Order By: Relevance
“…By contrast, antagonistic HMGB1 box A, miR-129-5p, and the natural product HMGB1 inhibitor glycyrrhizic acid reduce infarct size and tissue damage of the heart; inhibit oxidative stress and inflammatory response; and prevent pressure overload-induced cardiac hypertrophy, heart fibrosis, and failure [ 144 147 ]. Importantly, HMGB1 promotes NETs and exacerbates tissue damage [ 148 , 149 ]. Furthermore, soluble FN-EDA is a valuable biomarker in cardiac remodeling, and in patients with HF, the serum FN-EDA level was significantly elevated [ 150 ].…”
Section: Damage-associated Molecular Patterns and Cytokines Linkinmentioning
confidence: 99%
“…By contrast, antagonistic HMGB1 box A, miR-129-5p, and the natural product HMGB1 inhibitor glycyrrhizic acid reduce infarct size and tissue damage of the heart; inhibit oxidative stress and inflammatory response; and prevent pressure overload-induced cardiac hypertrophy, heart fibrosis, and failure [ 144 147 ]. Importantly, HMGB1 promotes NETs and exacerbates tissue damage [ 148 , 149 ]. Furthermore, soluble FN-EDA is a valuable biomarker in cardiac remodeling, and in patients with HF, the serum FN-EDA level was significantly elevated [ 150 ].…”
Section: Damage-associated Molecular Patterns and Cytokines Linkinmentioning
confidence: 99%
“…Leukocyte flux and leukocyte endothelium interactions (rolling and adhesion) analysis was conducted as described by Wang et al. ( 2019 ). Briefly, rolling leukocyte flux was measured at indicated time points by counting the number of rolling leukocytes per 20 s passing a reference point in the microvessel and expressed as cells/min.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of microvascular blood flow velocity in cremaster and leukocyte adhesion in venules were completed by Image-Pro Plus 6.0 software (Media Cybernetic, Rockville, MD) (Zhang et al 2019). Leukocyte flux and leukocyte endothelium interactions (rolling and adhesion) analysis was conducted as described by Wang et al (2019). Briefly, rolling leukocyte flux was measured at indicated time points by counting the number of rolling leukocytes per 20 s passing a reference point in the microvessel and expressed as cells/min.…”
Section: Cremaster Microcirculation Assessmentmentioning
confidence: 99%
“…1 ) ( 41 ). In addition, Wang et al found that neutrophil extracellular trap-MP complexes can promote the intrinsic pathway of coagulation in a sepsis mouse model; t hey subsequently found that neutrophil extracellular trap-MP complexes can trigger inflammation by mediating neutrophil aggregation through HMGB1-TLR2/TLR4 signaling ( 42 , 43 ). Damaged endothelial cells and epithelial cells are also found to release MPs in a number of respiratory diseases, such as chronic obstructive pulmonary disease, asthma, pulmonary fibrosis and pulmonary hypertension ( 44 ).…”
Section: Mechanisms Of Hypercoagulability In Covid-19mentioning
confidence: 99%